2019
DOI: 10.25035/jade.01.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Wearable GPS Devices in a British Elite Soccer Academy Setting: A Foucauldian Disciplinary Analysis Of Player Development And Experience

Abstract: Conventional wisdom dictates that the use of GPS surveillance technology in sport to assist athletic performance is an overwhelmingly positive phenomenon. Specifically, the health and performance benefits of the application of GPS and surveillance technologies have been well documented across a range of field sports. Previous research into the developmental implications of GPS surveillance in professional rugby league (Jones, Marshall, & Denison, 2016) has identified that there are some significant unintended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…These mediators can have a strong influence on players and their performance, as well as their attitudes to pain and injury [ 15 ]. These social influences have shaped an athlete’s attitude towards Sports Science and Medicine practices, and practitioners as sources of authority [ 16 ], and the worth of output monitoring in general (for example, in field sports such as football it has recently been reported that some athletes disdain load monitoring practices as superfluous [ 17 ].…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…These mediators can have a strong influence on players and their performance, as well as their attitudes to pain and injury [ 15 ]. These social influences have shaped an athlete’s attitude towards Sports Science and Medicine practices, and practitioners as sources of authority [ 16 ], and the worth of output monitoring in general (for example, in field sports such as football it has recently been reported that some athletes disdain load monitoring practices as superfluous [ 17 ].…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…However, despite the perceived benefits of subjectively monitoring RPE, recently, authors have cautioned that athlete subjective monitoring should not automatically be accepted as "universally beneficial" (23) and its use should be carefully monitored and routinely reviewed. Moreover, concerns have also been raised regarding the use of other surveillance technologies that adopt objective monitoring (e.g., Global Positioning Systems) (25). We also feel that similar concerns need to be raised regarding the appropriateness of a routine application of session RPE in elite sport settings.…”
Section: Load Monitoring and The Production Of "Docile Bodies"mentioning
confidence: 99%
“…The norm defines a standard or criteria of judgment; thus, identifying all those who do not meet the standard. In an applied sporting context, this failure to adhere to a prescribed norm may create a tense situation and prove problematic for the athlete (25). For example, if an athlete's RPE score does not conform to their teammates or the coach's RIE, they may be challenged as to why this is the case.…”
Section: Load Monitoring and The Production Of "Docile Bodies"mentioning
confidence: 99%
See 1 more Smart Citation
“…. normalise individuals into useful, docile bodies' (p. 73) has been taken up by a range of scholars investigating sports coaching (Denison 2007;Denison et al 2013Denison et al , 2017Denison and Mills 2014;Denison 2013, 2018;Mills et al 2020), strength and conditioning practices in sport (Gearity and Mills 2012), the implications of surveillance and wearable technologies in sport (Jones and Denison 2018;Jones 2019), as well as retirement from professional sport (Jones and Denison 2017). Lee Sinden (2013) has gone so far as to 5 Goffman's later work has also been appropriated for developing critical understandings of sport.…”
Section: Towards a Sociology Of Sport For Sports Chaplainsmentioning
confidence: 99%